EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DI DESA LOLI TASIBURI KECAMATAN BANAWA KABUPATEN DONGGALA - Akbar, Hary; Pasinringi, Andi; Ambo, Nur Aisyah (Katalogis, 2019)
The purpose of this study was to determine the effectiveness of Village Fund Allocation Management in Loli Tasiburi Village, Banawa District, Donggala Regency. The theoretical foundation used is Gibson (2005: 107) to see the effectiveness of village fund allocation management using seven indicators, namely the clarity of the objectives to be achieved; clarity of strategies to achieve objectives, a healthy process of analysis and formulation of policies, careful planning, appropriate programming, availability of infrastructure and facilities, an educational supervision and control system. This type of research is Qualitative Descriptive which seeks to interpret and interpret pleasant data with facts, using purposive methods, data collection and discussion with a qualitative analysis approach to collect data and materials through observation and interviews with a number of 5 (five) informants. Based on the results of the interview, it is known that Loli Tasiburi Village has not managed the village fund allocation maximally. This is due to the results of research that shows that indicators of careful planning, appropriate programming, and a system of supervision and supervision of education are not optimal because of the low level of community participation and each stage of Management of Village Fund Allocation not in accordance with management principles and allocation objectives Village Fund that prioritizes information transparency to the community